Anatomy of a false confession: the interrogation and conviction of Brendan Dassey - Cicchini, Michael D. (Rowman & Littlefield, 2018)
Brendan Dassey's confession -- From black box to glass house -- "People who are innocent don't confess," do they? -- Don't let facts get in the way -- Location, location, location -- Miranda to the rescue? -- Bypassing Miranda -- Overcoming Miranda -- Negating Miranda -- Getting to know all about you -- Scared straight -- Promises, promises -- Wordplay -- It's better to give than to receive -- Baby steps -- "It's not your fault" -- Positive feedback -- "Would you like a sandwich?" -- Remaining overconfident -- Pulling the rug from under -- Poisoning the jury pool -- Spit shining the evidence -- A simple plan -- Getting lucky at trial -- Mailing in the appeal -- Reversal of fortune -- The aedpa: "a formidable barrier" -- Too close for comfort -- Law is dead -- Stare decisis -- What if? -- Reforming Miranda -- Role-playing interrogators -- False confession experts at trial -- Bye bye Reid? -- The dangers of discourse -- Calling the Supreme Court